New Keystone flap application in vulvo-perineal reconstructive surgery: A case series - Michele Peiretti; Elisabetta Corvetto; Giorgio Candotti; Stefano Angioni; Andrea Figus; Valerio Mais (Elsevier, 2019)
Objective: This study aimed to evaluate the application of the Keystone flap technique and the long-term results of vulvovaginal reconstruction after vulvar surgery. Methods: This is the first case series describing the application of the Keystone perforator island flaps (KPIF) technique to close a wide defect after radical vulvectomy. We prospectively collected patient demographics, operative times, complications, pathologic results, and length of stay on all patients. The benefits, cosmetic results and satisfaction of patients were analyzed in the follow up. Results: Five patients were selected for the study: four underwent radical vulvectomy for squamous cell vulvar cancer, and one underwent vulvar wide excision for Paget disease followed by reconstruction with the Keystone flap technique. The defects were successfully covered by the Keystone flap technique in all patients. Conclusions: Keystone flaps seem to be easy to design and elevate, and it offers rapid fasciocutaneous closure in wide vulvo-perineal defects with excellent long-term results. Keywords: Vulvar cancer, Key stone flap, Reconstructive surgery